Respuesta :

Answer:

[tex]x=0\\y=-3[/tex]

Step-by-step explanation:

[tex]-5x+y=-3\\3x-8y=24[/tex]

Let's solve the first equation for y to later on replace it in the second.

[tex]y=-3+5x[/tex]

Now plug this in the second equation.

[tex]3x-8y=24\\3x-8(-3+5x)=24\\[/tex]

Distribute -8

[tex]3x+24-40x=24\\[/tex]

Subtract 24

[tex]3x-40x=24-24[/tex]

Combine like terms;

[tex]-37x=0[/tex]

Divide by -37

[tex]x=\frac{0}{-37}\\ x=0[/tex]

Now replace x in any of the equations to find y.

[tex]-5x+y=-3\\-5(0)+y=-3\\y=-3[/tex]

Answer:

x = 0,

y = -3

Step-by-step explanation:

Let us solve through elimination ~

1. Multiply top equation -5x + y = -3 by 8, adding that product to the bottom equation 3x - 8y = 24:

 8 ( -5x + y = -3)     ⇒    - 40x + 8y = -24    

+  3x - 8y = 24             +    3x  -  8y = 24

2. To further express this algebraic process of adding to find x in this case:

- 40x + 8y = -24       ⇒     - 37x = 0     ⇒     x = 0

+    3x  -  8y = 24

3. Now let us substitute this value of x into the top equation -5x + y = -3:

- 5 ( 0 ) + y = - 3    

4. ...And solve for y:

- 5 ( 0 ) + y = - 3    ⇒    0 + y = -3    ⇒    y = -3